Empirical Analysis of Innovation-Driven Strategies on Vocational School Graduate Competitiveness in the Industry 4.0 Era - Chaerunnisa; Heny Hendrayati; Ratih Hurriyati; Puspo Dewi Dirgantari; Budi Harto (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The fourth industrial revolution has changed the economic landscape and labor market, creating disruption in various sectors and increasing demand for graduates with 21st-century skills. However, there is a striking difference between the competencies of vocational high school graduates and the growing needs of industry 4.0, as evidenced by the high unemployment rate. Previous research on the impact of transformational leadership, industry partnerships, and teacher talent management on graduate competitiveness has often shown inconsistent results and indicated the presence of a suspected mediating factor, namely school innovation culture. This study is explanatory and quantitative, applying a Partial Least Squares Structural Equation Modeling approach involving 150 respondents from vocational high schools. The analysis shows that industry partnerships have an influential and largest direct effect on school innovation culture (β=0.698) and graduate competitiveness (β=0.667). Furthermore, teacher talent management contributes (β=0.251) to graduate competitiveness. School innovation culture shows an influential mediating role in the relationship between industry partnerships and graduate competitiveness (β=0.151), but has no effect on the relationship with other strategic variables. These findings indicate the importance of strengthening strategic industry partnerships and the need to implement concrete innovation incentive policies to accelerate the transformation of vocational schools.